Antecedents of Viewers’ Live Streaming Watching: A Perspective of Social Presence Theory - Chen, Jiada; Liao, Junyun (Frontiers in Psychology, 2022)
Live streaming commerce as a popular marketing method has attracted wide attention, but little is known about why consumers continue to watch live streaming. To fill this research gap, this study draws on social presence theory to examine the impact of sense of community, emotional support, and interactivity on viewers' social presence, which, in turn, influences their live streaming watching. Furthermore, the moderating role of streamer attractiveness is also investigated. The authors collected survey data from 342 live streaming viewers and used the structural equation model to test the research model. The results reveal that sense of community, interactivity, and emotional support positively affects viewers' social presence, leading to viewers' watching live streaming. Furthermore, streamer attractiveness plays a significant moderating role between social presence and live streaming watching. This study provides a unified theoretical framework to explain the intention to watch live streaming based on social presence theory.